Longitudinal CNS and systemic T-lymphocyte and monocyte activation before and after antiretroviral therapy beginning in primary HIV infection - Chan, Phillip; Li, Xiang; Li, Fangyong; Emu, Brinda; Price, Richard W.; Spudich, Serena (Frontiers in Immunology, 2025)
BackgroundTrafficking of immune cells to the central nervous system is hypothesized to facilitate HIV entry and immune-induced neuronal injury and is mediated by surface proteins such as chemokine receptors and α4 integrin. We longitudinally assessed immune cell activation and surface marker expression in cerebrospinal fluid (CSF) and blood and their relationship with CSF HIV RNA beginning during primary HIV infection (PHI) before and after antiretroviral therapy (ART).MethodsLongitudinal paired blood and CSF were obtained in ART-naïve PHI (<12 month since infection) participants; some independently initiated ART during follow up. Multiparameter flow cytometry of fresh samples determined activation (% CD38+HLADR+) and chemokine receptor expression (% CCR5+ and CXCR3+) on CD4+ and CD8+ T cells, and subtype and α4 integrin expression (% and mean fluorescence intensity (mfi) of CD49d+) on monocytes. HIV RNA was quantified by PCR. Analyses employed Spearman correlation, within-subject correlation, and linear mixed models.Results51 participants enrolled at a median 3.2 months post HIV transmission with 168 total visits (113 pre-ART, 55 post-ART) and a median of 6.5 months of longitudinal follow up (range 0-40). In pre-ART PHI, frequencies of activated CD4+ and CD8+ T cells were much higher in CSF than in blood, with levels similar to ART-naïve people with chronic HIV infection. Both CSF CD4+ and CD8+ T cell activation increased longitudinally prior to initiation of ART. In multivariate analysis, CSF CD4+ but not CD8+ T cell activation independently predicted CSF HIV RNA. Neither CSF monocyte subtypes or α4 expression correlated with CSF HIV RNA. Blood monocyte α4 MFI correlated with CD4+ and CD8+ T cell activation (p<0.05). Following ART initiation, blood but not CSF T cell activation declined with days on treatment (slope=-0.06, p=0.001). During ART, blood and CSF monocyte α4 MFI correlated with T cell activation (p<0.05).ConclusionsIn untreated early infection after PHI, immune activation increases over time, and CSF CD4+ T cell activation but not monocyte activation correlates with CSF HIV RNA. Intrathecal T cell activation does not decline during early follow up on ART. Immunomodulating therapies may be needed to prevent neuronal injury and HIV neuroinvasion during early HIV.